Assessment of metal species in river Ganga sediment at Varanasi, India using sequential extraction procedure and SEM–EDS. (September 2015) - Pandey, Mayank; Pandey, Ashutosh Kumar; Mishra, Ashutosh; Tripathi, B.D.
Highlights: The present study is first of its kind in the studied region. It deals with impact assessment of urban drains on river water and sediment. Metal speciation analysis was carried out by sequential extraction procedure. EDX study of the sediment was conducted to assess the elemental composition. Abstract: Aim of the present study was to assess impact of urban drains over river water and sediments by physico-chemical and metal analysis. Metal speciation (Sequential Extraction Procedure) and elemental composition analysis (SEM–EDS) was used to quantify metal pollution load in river sediments. Metal speciation analysis showed dominance of available and labile fractions of all heavy metals (Cr, Ni, Cu, Zn, Cd and Pb) except Mn and Fe which were dominant in residual forms. Cluster analysis (CA), Principal Components Analysis (PCA) and Partial Least Square Regression (PLSR) were applied as source receptor modeling for pollutants. Results classified river stretch into three zones i.e. moderately, severely and extremely polluted, on the basis of pollutant concentration released from anthropogenic sources. SEM–EDS study revealed the elemental composition percentage in river sediments. Pollution Load Index (PLI) varied from 1.8 (S1)–3.9 (S15). The Geo accumulation index (GAI) was found highest for Cd (6.88–8.97) and Pb (2.41–3.24).